1997
DOI: 10.1128/jb.179.18.5712-5719.1997
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a chemotaxis operon from Rhodospirillum centenum

Abstract: A chemotaxis gene cluster from the photosynthetic bacterium Rhodospirillum centenum has been cloned, sequenced, and analyzed for the control of transcription during swimmer-to-swarm cell differentiation. The first gene of the operon (cheAY) codes for a large 108-kDa polypeptide with an amino-terminal domain that is homologous to CheA and a carboxyl terminus that is homologous to CheY. cheAY is followed by cheW, an additional homolog of cheY, cheB, and cheR. Sequence analysis indicated that all of the che genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…If so, then disruption of cheY may have a significant effect only on swarmer cell motility. While we have no direct evidence for the existence of separate motors, sequence comparison of the motor docking domains of CheY and CheAY indicated that they are quite different (see the accompanying report [15]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If so, then disruption of cheY may have a significant effect only on swarmer cell motility. While we have no direct evidence for the existence of separate motors, sequence comparison of the motor docking domains of CheY and CheAY indicated that they are quite different (see the accompanying report [15]). …”
Section: Discussionmentioning
confidence: 99%
“…An added complexity is presented by the control of rotations of lateral and polar flagella, which appear to utilize different structural components (13,34). To examine some of these issues, we have undertaken a mutational analysis of the R. centenum chemotaxis signal transduc-tion cascade, which exhibits several unique features (see the accompanying report [15]). For this analysis, we used reverse genetics techniques to construct nonpolar insertion mutants in individual genes in the che operon.…”
mentioning
confidence: 99%
“…Moreover, 50% to 60% of mesophilic aeromonads are able to produce many unsheathed peritrichous lateral flagella when grown in viscous environments or over surfaces (58), which increase bacterial adherence and are required for swarming motility and biofilm formation (23). The expression of two distinct flagellar systems is relatively uncommon, although it has been observed with Vibrio parahaemolyticus (39), Azospirillum brasilense (45), Rhodospirillum centenum (32), Helicobacter mustelae (49), and Plesiomonas shigelloides (29).…”
mentioning
confidence: 99%
“…The expression of two distinct flagellar systems is relatively uncommon, although it has been observed in Vibrio parahaemolyticus (19), Azospirillum brasilense (26), Rhodospirillum centenum (15), Helicobacter mustelae (29), and Plesiomonas shigelloides (13). V. parahaemolyticus is the best-studied organism, and it has two distinct flagellar systems.…”
mentioning
confidence: 99%